Evaluation of anthelmintic efficacy of triclabendazole, nitroxynil and albendazole against naturally acquired fascioliasis in cattle of Bangladesh with special reference to its residual effect - Aktaruzzaman, Md.; Mohamed, Zahurin; -Ul-Alam, Naim; Islam, Md. Siddiqu; Howlader, Md. Matiar Rahman (International Journal of Pharmacology and Toxicology, 2015)
This study aimed to evaluate the efficacy of triclabendazole, nitroxynil and albendazole against fascioliasis in naturally infected cattle of government dairy farm, Sylhet, Bangladesh. The study included 50 cattle breed of which 30 were naturally infected and randomly selected 20 based on their weight and egg count. Twenty cattle of 2-3 years old irrespective of sex infested with fascioliasis were selected for this experiment and randomly divided into four equal groups (group A, B, C and D) where each group consisted of 5 cattle and cattle of group D were kept as control group. One injectable nitroxynil (10 mgkg-1 body weight, S/C) preparations (Renata Ltd. Bangladesh) and two solid triclabendazole, albendazole (12 mgkg-1, 15 mgkg-1 body weight, orally) preparations (Novartis Ltd. and Square Pharmaceuticals Ltd. Bangladesh) were used for positive control of fascioliasis as group A, B and C. Cattle of group D was kept as control without giving any treatment. Before trials (day 0), total egg count, blood samples and initial body weight were recorded. During the study period the fecal and blood samples were collected directly from rectum and examined on 7th, 14th, 21st and 28th day using McMaster fecal egg counting method. Body weight was recorded on day 28 following the treatments. The therapeutic efficacy was evaluated through determination of parasitic prevalence, body weight gain/loss and hematological findings. Pre and post-treatment EPG (eggs per gram) values were recorded, and efficacies compared. The results showed that the efficacy of nitroxynil was 92.57%, followed by triclabendazole 91.55% and albendazole 84.53%, which were significant (p<0.01). The observed differences in efficacy between these three brands of anthelmintics were most likely due to variations either in quality or the administered doses. The body weight of the treated animals was increased, which were significant (p<0.01). After treatment triclabendazole, nitroxynil and albendazole, Total Erythrocyte Count (TEC), Hemoglobin (Hb) content and Packed Cell Volume (PCV) were increased significantly (p<0.01 and p>0.05) in cattle but Erythrocyte Sedimentation Rate (ESR) and Total Leukocyte Count (TLC) were decreased significantly (p<0.05 and p>0.01) in all treated cattle and body weight was increased significantly (p<0.01) on day 28. Â The farm management practices along with results of the present study revealed the efficacy of multiple anthelmintics against fascioliasis in cattle. Additional detailed studies are required to clarify the current status of the efficacy of the anthelmintics widely used in different agro ecologies, animal species, and livestock management systems in Bangladesh.